COST STRUCTURE AND SHAREHOLDER WEALTH MAXIMISATION AMONG LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2025)
The study examined the effect of cost structure on shareholder wealth maximisation among listed manufacturing firms in Nigeria. The specific objective was to ascertain the effect of cost of sales, cost of selling and marketing, staff cost and administrative cost on the shareholder return of listed manufacturing firms in Nigeria. Ex-post facto research design was adopted in the study. Twenty listed consumer goods firms made up the population of the study while purposive sampling was used to select fifteen listed consumer goods firms. Secondary data used were sourced from the annual reports of the firms over an eleven year period from 2014 to 2024. Preliminary analyses were done using descriptive test, correlational analysis, linearity test, chow test, heteroskedasticity test, autocorrelation test, and cross-sectional dependence test. Hypotheses were tested using panel estimated generalised least square regression. The study found that: cost of sales has a positive and significant effect on shareholder return of listed manufacturing firms in Nigeria (β = 0.0384, p = 0.0000); cost of selling and marketing also exerts a positive and significant effect on shareholder return of listed manufacturing firms in Nigeria. (β = 0.0216, p = 0.0326); staff cost shows a negative and highly significant effect on shareholder return of listed manufacturing firms in Nigeria (β = -0.3162, p = 0.0000); administrative cost has a positive and significant effect on shareholder return of listed manufacturing firms in Nigeria (β = 0.2023, p = 0.0002). In conclusion, not all cost components carry equal weight in shareholder wealth outcomes, and that the structure and composition of firm expenditures play a decisive role in influencing the financial rewards shareholders derive from their investment. The study recommends that production and supply chain directors of listed manufacturing firms in Nigeria should prioritise strategic investments in raw material sourcing, inventory control systems, and production efficiency technologies
Keywords: Cost Structure; Cost of Sales; Cost of Selling; Shareholder Return; Shareholder Wealth Maximisation